2017
DOI: 10.18632/oncotarget.23192
|View full text |Cite
|
Sign up to set email alerts
|

Src is the primary target of aripiprazole, an atypical antipsychotic drug, in its anti-tumor action

Abstract: Aripiprazole (ARP) is an atypical anti-psychotic drug widely used to treat schizophrenia and bipolar disorder. The pharmacological effects of ARP on cancer cells are still poorly understood. In this study, anti-cancer effects of ARP on various malignant tumor cells and its molecular mechanism were further carefully examined by using cell proliferation assay, xenograft mouse model, immunoblotting analysis, migration assay, luciferase reporter gene assay, kinase assay, and overexpression strategy. Treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 55 publications
2
25
0
1
Order By: Relevance
“…Taken together, it seems that this drug can be mentioned as a good cytotoxic compound. As reported here, the cytotoxicity of aripiprazole on MKN45 cancer cell line is consistent with some other researches (5,21) . Anti-cancer effects of aripiprazole on various malignant tumor cells and its molecular mechanism were examined by using cell proliferation assay, xenograft mouse model, immunoblotting analysis, migration assay, luciferase reporter gene assay, kinase assay, and overexpression strategy.…”
Section: Mtt Assaysupporting
confidence: 93%
See 2 more Smart Citations
“…Taken together, it seems that this drug can be mentioned as a good cytotoxic compound. As reported here, the cytotoxicity of aripiprazole on MKN45 cancer cell line is consistent with some other researches (5,21) . Anti-cancer effects of aripiprazole on various malignant tumor cells and its molecular mechanism were examined by using cell proliferation assay, xenograft mouse model, immunoblotting analysis, migration assay, luciferase reporter gene assay, kinase assay, and overexpression strategy.…”
Section: Mtt Assaysupporting
confidence: 93%
“…Anti-cancer effects of aripiprazole on various malignant tumor cells and its molecular mechanism were examined by using cell proliferation assay, xenograft mouse model, immunoblotting analysis, migration assay, luciferase reporter gene assay, kinase assay, and overexpression strategy. Treatment with aripiprazole induced cytotoxicity in U251 glioma cells, MKN-1 gastric adenosquamous carcinoma cells, and CT26 colon carcinoma cells (5) . Moreover, the effects of aripiprazole alone and in combination with chemotherapeutic agents in order to test growth ability, the ability to form stem cells/differentiation/ chemical resistance, the markers of cancer stem cells, cancer cells and normalized cells was investigated.…”
Section: Mtt Assaymentioning
confidence: 96%
See 1 more Smart Citation
“…The transition between adaptive to terminal UPR is dependent on the stressor and the cell type. Cytotoxicity of Ari has been previously demonstrated, but the mechanism is not well understood and was postulated to involve inhibition of tyrosine kinases such as Src and Syk (Kim et al, 2017;Yoo et al, 2018). In dopaminergic neurons, Ari protected from glutamate-induced cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Aripiprazole is also an atypical antipsychotic which is widely used to treat schizophrenia. Kim et al ( 2018 ) recently proved that aripiprazole inhibits the glioma cell migration and induces apoptosis by directly inhibiting oncogenic Src kinase. It has been reported that the Src and Akt are common downstream signaling kinases of BDNF (Zhang et al, 2013 ), so these findings are consistent with the increase of BDNF in glioma patients.…”
Section: The Similar Mechanisms Involved In Glioma Tumorigenesis and mentioning
confidence: 99%